OC-070 Ml:8: a novel surgical irrigant reduces viable bacterial load in sheets of human colon ex vivo. (22nd June 2015) - Mcdermott, FD; Folan, D; Winter, DC; Folan, MA; Baird, AW
Abstract : Introduction: ML:8 is a proprietary emulsion of fatty acids and triglycerides with efficacy at eliminating biofilms, and has been evaluated as a central line locking solution. These components are potentially less toxic than more traditional chlorhexidine or iodine. With increasing incidence of resistant bacteria and interest in the colonic microbiome; a surgical irrigation ML:8 formulation was developed that may have experimental and clinical applications. The aim was to test efficacy and effect of ML:8 on ex-vivo human colonic tissues compared to current solutions in clinical use. Method: Human tissues obtained from healthy margin of freshly resected sigmoid colon. Tissues exposed for 2 min to one of 4 solutions: Control Krebs Henseleit (KH), 0.9% NaCl, 1% povidone iodine (I2 ), 2% ML:8 n = 4. Mucosal surfaces swabbed for culture using Petrifilms®. Colony forming units (CFUs) counted at 48 h by 2 blinded operators. Mucosal sheets mounted in Ussing chambers with KH (37 o C, 95% O2 /5% CO2 ) and voltage clamped. At the end tissues challenged with muscarinic agonist, carbachol as a marker of epithelial function. Permeability coefficient (Papp) was derived using [ 14 C] mannitol. Tissues were fixed in formalin for histology. Results: Similar CFUs grew in aerobic and anaerobic conditions in control and NaCl tissues. I2 reduced (p < 0.05) and ML:8 virtually abolished viable bacteria (p < 0.05). Short circuit current (SCC; μA/cm 2 ) and Potential difference (PD; mV) not different between treatments. SCC at time 0: –34.2 ± 6.0, –35.4 ± 10.8, –27.0 ± 2.8, –42.3 ± 4.3 for KH, NaCl, I2 and ML-8 respectively (p = 0.11). PD time 0: –5.8 ± 2.4, 2.9 ± 0.5, –3.6 ± 0.4, –3.2 ± 1.1 (p = 0.24). Transepithelial Electrical Resistance (TEER Ω.cm 2 ) higher in control group: 118.5 ± 29.2, 47.7 ± 16.4, 92.0 ± 15.4, 69.8 ± 11.5 but did not reach significance (p = 0.05). Tissues responded to carbachol although attenuated in I2 treated tissue (p = < 0.05). Papp higher in all treated tissues but this did not reach significance (p = 0.07). Histopathological assessment revealed no overt damage to tissues and crypt heights uniform. Conclusion: ML:8 rapidly and effectively reduced bacterial counts with no adverse effects on a broad range of functional and structural parameters on human colonic mucosa ex vivo . This represents a potentially powerful tool for exploring mechanisms of host-microbiome interactions similar to gnotobiotic animal models. Brief exposure to ML:8 had comparable outcomes to control treated tissues and possibly less impact than iodine. These are early experiments but potential future clinical applications of ML:8 include decolonisation for elective surgery, prior to faecal transplantation for C.difficile or for surgical sepsis e.g. perforated colon. Disclosure of interest: F. Mcdermott: None Declared, D. Folan: None Declared, D. Winter: None Declared, M. Folan Conflict with: Company Director of Capstan Healthcare Ltd, A. Baird Conflict with: Company Director of Capstan Healthcare Ltd.